Implementasi IoT Untuk Early Warning System(EWS) Pada Tambak Udang Vaname - Muhamad Wisnu Alfiansyah; I Gede Putu Wirarama Wedashwara W; Ahmad Zafrullah Mardiansyah (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
Vaname shrimp is a type of aquaculture that has a high economic value and has relatively fast growth. Good water quality is key in the cultivation of vaname shrimp on ponds. However, monitoring of pond water conditions is still done manually and not done intensively. Internet of Things (IoT) and Early Warning System (EWS) as the latest technology can be a solution in periodic pond monitoring activities and give early warning to farm owners. Double Exponential Smoothing Holt is one method for forecasting in time series. In this study, the system predicts the potential for endangering the pond conditions, when there are indications of danger, it will inform the user via Telegram chat. The accuracy test value of the forecasting method used for water temperature is the MSE value of 0.01954 and MAPE of 9.0859%. Whereas for the water pH, the MSE value is 0.000155 and MAPE of 0.828%.